EVALUATION OF ANTI-INFLAMMMATORY ACTIVITY OF METHANOLIC EXTRACT OF CESTRUM NOCTURNUM AND TECTONA GRANDIS (International Journal of Food and Nutritional Sciences, 2022)
The methanolic extract of Cestrum nocturnum bark given by oral route in rats showed a significant and dose-dependent anti-inflammatory activity by paw edema method used. The better activity was found at a dose of 30 mg/kg when compared to reference drug. The phenyl butazone was used as reference drug (100mg/kg). and methanolic extract of Tectona grandis leaves given by oral route in mice showed a significant and dose-dependent anti-inflammatory at a dose of 250 mg/kg when compared to reference drug. The Ibuprofen was used as reference drug (10mg/kg). From these results it is clear that the methanolic extract of the fruits of Tectona grandis posses’ anti-inflammatory activity and this justify the folklore use of this plant.The study indicates the potential of these extracts as anti-inflammatory drugs. The activity may be attributed to the inhibition of the COX-2 enzyme or inhibition of the activation of transcription factors. The study validated the methanolic extract of Tectona grandis fruit towards management of pain and inflammation. The exact role of individual phytoconstituents needs to be illustrated using suitable bio-analytical techniques to extrapolate exact mechanism of their action